Evaluating the Benefits and Drawbacks of Visualizing Systems Modeling Language (SysML) Diagrams in the 3D Virtual Reality Environment - Lutfi, Mostafa; Valerdi, Ricardo (Systems (Basel), 2025)
Model-Based Systems Engineering (MBSE) prioritizes system design through models rather than documents, and it is implemented with the Systems Modeling Language (SysML), which is the state-of-the-art language in academia and industry. Virtual Reality (VR), an immersive visualization technology, can simulate reality in virtual environments with varying degrees of fidelity. In recent years, the technology industry has invested substantially in the development of head-mounted displays (HMDs) and related virtual reality (VR) technologies. Various research has suggested that VR-based immersive design reviews enhance system issue/fault identification, collaboration, focus, and presence compared to non-immersive approaches. Additionally, several research efforts have demonstrated that the VR environment provides higher understanding and knowledge retention levels than traditional approaches. In recent years, multiple attempts have been made to visualize conventional 2D SysML diagrams in a virtual reality environment. To the best of the author’s knowledge, no empirical evaluation has been performed to analyze the benefits and drawbacks of visualizing SysML diagrams in a VR environment. Hence, the authors aimed to evaluate four key benefit types and drawbacks through experiments with human subjects. The authors chose four benefit types—Systems Understanding, Information Sharing, Modeling and Training Experience, and Digital Twin based on the MBSE value and benefits review performed by researchers and benefits claimed by the evaluations for similar visual formalism languages. Experiments were conducted to compare the understanding, interaction, and knowledge retention for 3D VR and conventional 2D SysML diagrams. The authors chose a ground-based telescope system as the system of interest (SOI) for system modeling. The authors utilized a standalone wireless HMD unit for a virtual reality experience, which enabled experiments to be conducted irrespective of location. Students and experts from multiple disciplines, including systems engineering, participated in the experiment and provided their opinions on the VR SysML implementation. The knowledge test, perceived evaluation results, and post-completion surveys were analyzed to determine whether the 3D VR SysML implementation improved these benefits and identified potential drawbacks. The authors utilized a few VR scenario efficacy measures, namely the Simulation Sickness Questionnaire (SSQ) and System Usability Scale (SUS), to avoid evaluation design-related anomalies.